Sufi Influences In Fouad Haddad's Poetry/ الآثار الصوفية في شعر فؤاد حداد - Moursi, Abdullah Ramadan Khalaf; Abdel-Ati, Ahmed Ali Mohamed; Salem, El Sayed Mohamed; Fath El-Bab, Mohamed Salah El-Din Ahmed (Ijaz Arabi Journal of Arabic Learning, 2025)
This research aims to demonstrate the Sufi influences of the Egyptian colloquial poet Fouad Haddad, and these influences appeared in two forms: The first is the presence of Sufi scholars and poets, by bringing their ideas and poems to life by directly and indirectly quoting them in his poems and adding his spirit to them. As well as the presence of Sufi symbols and customs and his use of symbolism to express his appreciation for the idea of Sufism, its spirit, and its representation in his poetry. The researchers used the descriptive analytical approach to study the phenomenon of Sufism in the poetry of Fouad Haddad to solve the problem of the study, which was represented in the central question: How did the poet Fouad Haddad express his love for Sufism and how did he describe the spirit of Islamic Sufism, its scholars, and its poets? How did he use colloquial poetry to highlight the value and spirit of Islamic Sufism? The research concluded with a set of results, the most prominent of which is The emergence of Sufi influences, as more than one Sufi poet is present, either by his explicit name by calling upon one of his creative texts or even by invoking his method of praise or his style of divine love. These Sufi influences also appear in Fouad Haddad's creativity, with many symbols and styles of speech and expression. His use of the words of Sufis or their poets in a direct intentional quotation symbolizes an idea, vision, political or religious trend that the poet wants to convey to the recipient, hence the importance of this research.